Maths Talk: The Voices of Teachers in Irish Classrooms - O'Connor, Michelle (Marino Institute of Education, 2024)
A new Primary Mathematics Curriculum is due to be operational in Irish classrooms in September 2024. One of the five key pedagogies of this new curriculum is Maths Talk, yet little is known about how teachers can be supported to implement in their classrooms. This qualitative case study was situated in the context of the roll-out of the New Primary Mathematics Curriculum. It examined what supports teachers perceived they had or needed to implement Maths Talk in their classrooms. It. Four mathematics lessons were observed in first and second class. These observations were analysed thematically and that analysis contributed to the structure of a focus group, together with themes that emerged from a review of literature. Particular attention was paid to teacher moves such as questioning and explaining. The second stage of this research comprised of a focus group populated by the four observed teachers and the SET teachers who supported their rooms. It was found that teachers are supported by their knowledge of subject and their students. When resources are plentiful and time is abundant, they perceived Maths Talk lessons to be a positive experience. They were bolstered by positive mindsets that were evident in their students. On the other hand, teachers identified numerous factors that they needed support with. Dealing with frustrated students with emerging language trying to communicate, and running out of time to hear all children’s contributions were but two of these factors. The findings of this study have many implications for policy makers both at national and school level. Teacher’s perceptions were, when it comes to implementing Maths Talk in their classrooms, they need a lot of support.
Keywords: Education; Primary; Primary school teachers; Qualitative research; Irish Primary Curriculum; Focus Group; Observation; Mathematics--Study and teaching